2009
DOI: 10.1007/s12565-009-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations in the tendon sheath of the first compartment

Abstract: Using Hiranuma's classification, we carefully examined anatomical variations in the first compartments of 246 human wrist joints from 124 cadavers. Morphological examinations were conducted to determine the number of accessory tendons and the existence of dissepiments for the extensor pollicis brevis (EPB) and abductor pollicis longus (APL) tendons. Anatomical variations of EPBs and APLs were grouped together by type, and appearance ratios were calculated based on Hiranuma's classification. Of the 246 wrist jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…We also observed that the frequencies of complete and incomplete septa were 44.4 and 55.5 %, respectively. Previous studies stated frequencies of a complete and incomplete septum as 23.2-53.5 % and 8.9-47 %, respectively [9,12,13,16,21]. Our results were coherent with the literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also observed that the frequencies of complete and incomplete septa were 44.4 and 55.5 %, respectively. Previous studies stated frequencies of a complete and incomplete septum as 23.2-53.5 % and 8.9-47 %, respectively [9,12,13,16,21]. Our results were coherent with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…A limitation of our study was our relatively small sample size in regard to previous cadaveric studies [9,12,16,21]. A second limitation was that once we opened the extensor sheath, it was impossible for us to evaluate the inner morphometry of the 1stEC.…”
Section: Discussionmentioning
confidence: 97%
“… 1 Multiple tendinous insertion of APL has been reported by many authors. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 The anatomical variation may remain asymptomatic or may present with painful conditions like de Quervain tenosynovitis (DQT). 2 5 6 19 The treatment of such condition in severe cases involves either an injection therapy or surgical decompression of the first extensor compartment.…”
Section: Introductionmentioning
confidence: 99%
“…The number of tendon slips on the APL side detected with US correlated with type of subcompartmentalization, was recorded as complete or distal incomplete ( 14,15 ) ( Fig 1 ). Complete subcompartmentalization was defi ned as the APL and EPB each running in a separate subcompartment at the level of distal radius, just after the crossover to the second extensor compartment.…”
Section: Number Of Tendon Slipsmentioning
confidence: 99%
“…In their large-scale anatomic study, Motoura et al ( 15 ) showed that anatomic variation in the fi rst compartment was as follows: normal type of de Quervain disease (Hiranuma type I) in 63.4% of cases, complete septation (Hiranuma type II) in 23.2%, incomplete septation (Hiranuma type III) in 8.9%, and EPB lacking type of de Quervain disease (Hiranuma type IV) in 4.5%. A study of 300 cadaveric wrists by Jackson et al ( 4 ) showed a 40% incidence of subcompartmentalization within the fi rst compartment, with one-third of subcompartmentalization (18%) being incomplete .…”
Section: Preoperative Us Findings and Surgical Findings In 15 Wrists mentioning
confidence: 99%